2001
DOI: 10.1136/adc.85.5.382
|View full text |Cite
|
Sign up to set email alerts
|

Mortality in severe meningococcal disease

Abstract: Aim-To evaluate mortality of critically ill children admitted with meningococcal disease. Methods-Prospective study of all children admitted to a regional paediatric intensive care unit (PICU) between January 1995 and March 1998 with meningococcal disease. Outcome measures were actual overall mortality, predicted mortality (by PRISM), and standardised mortality ratio. Results-A total of 123 children were admitted with meningococcal disease. There was an overall PICU mortality of 11 children (8.9%). The total m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(47 citation statements)
references
References 28 publications
2
43
0
2
Order By: Relevance
“…This led to the accelerated testing, licensing and introduction of the UK meningococcal group C conjugate vaccination programme [29]. Recent studies have shown that the case fatality rate of meningococcal disease can be reduced by improved clinical management in specialised centres [15,16]. However, attempts to further reduce mortality by better case management rather than by vaccination could be limited by the virulence of the infecting strain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This led to the accelerated testing, licensing and introduction of the UK meningococcal group C conjugate vaccination programme [29]. Recent studies have shown that the case fatality rate of meningococcal disease can be reduced by improved clinical management in specialised centres [15,16]. However, attempts to further reduce mortality by better case management rather than by vaccination could be limited by the virulence of the infecting strain.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that have been shown to affect the outcome of meningococcal disease include age [12,13], clinical presentation (with a higher case fatality rate associated with septicaemia than meningitis [12][13][14]), treatment factors [15,16] and the characteristics of the infecting organism, including serogroup and serotype [12,14,17,18]. Interventions to improve the outcome of meningococcal disease include the encouragement of early administration of penicillin [19].…”
Section: Introductionmentioning
confidence: 99%
“…Meningococcal case fatality has decreased in recent years, but meningococcal infection continues to be an important cause of mortality and morbidity in developing countries [1,24]. Mortality is higher in cases of shock and in infants [16].…”
Section: Introductionmentioning
confidence: 98%
“…In the United Kingdom, researchers from the Paediatric Intensive Care Society and the Meningitis Research Foundation conducted a successful campaign directed at parents to identify early signs of meningococcaemia, including petechiae and purpura (28). This was thought to be an important factor in improving outcomes for children with this condition (29,30). Work in many developing countries to create distributed primary healthcare networks (using untrained adults as community health-workers) has helped expand the model of teaching laypeople to recognize basic signs of distress in children.…”
Section: Discussionmentioning
confidence: 99%